Complement receptor C5aR1 on osteoblasts regulates osteoclastogenesis in experimental postmenopausal osteoporosis - Bülow, Jasmin Maria; Renz, Nikolai; Haffner-Luntzer, Melanie; Fischer, Verena; Schoppa, Astrid; Tuckermann, Jan; Köhl, Jörg; Huber-Lang, Markus; Ignatius, Anita (Frontiers in Endocrinology, 2022)
In recent years, evidence has accumulated that the complement system, an integral part of innate immunity, may be involved in the regulation of bone homeostasis as well as inflammatory bone loss, for example, in rheumatoid arthritis and periodontitis. Complement may also contribute to osteoporosis development, but investigation of the mechanism is limited. Using mice with a conditional deletion of the complement anaphylatoxin receptor C5aR1, we here demonstrated that C5aR1 in osteoblasts (C5aR1Runx2-Cre mice) or osteoclasts (C5aR1LysM-Cre mice) did not affect physiological bone turnover or age-related bone loss in either sex, as confirmed by micro-computed tomography, histomorphometry, and biomechanical analyses of the bone and by the measurement of bone turnover markers in the blood serum. When female mice were subjected to ovariectomy (OVX), a common model for postmenopausal osteoporosis, significant bone loss was induced in C5aR1fl/fl and C5aR1LysM-Cre mice, as demonstrated by a significantly reduced bone volume fraction, trabecular number and thickness as well as an increased trabecular separation in the trabecular bone compartment. Confirming this, the osteoclast number and the receptor activator of nuclear factor k-B (RANK) ligand (RANKL) serum level were significantly elevated in these mouse lines. By contrast, C5aR1Runx2-Cre mice were protected from bone loss after OVX and the serum RANKL concentration was normalized. These data suggested that bone cell-specific C5aR1 may be redundant in bone homeostasis regulation under physiological conditions. However, C5aR1 on osteoblasts was crucial for the induction of bone resorption under osteoporotic conditions by stimulating RANKL release, whereas C5aR1 on osteoclasts did not regulate OVX-induced bone loss. Therefore, our results implicate C5aR1 on osteoblasts as a potential target for treating postmenopausal osteoporosis.